COMPARISON OF INHIBITORY ACTIVITY AGAINST THE Î±-GLUCOSIDASE ENZYMES IN THE EXTRACTS AND FRACTIONS FROM LEAVES OF THE GARCINIA KYDIA ROXBURGH - Martha, Septiani; Elya, Berna; Hanafi, Muhammad (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective : Garcinia kydia Roxb. is aspecies of the genus Garcinia, is based chemotaxonomic has various bioactive compounds that have been isolated by a variety of pharmacological activities, one of the activities that are being developed that inhibition ofÂ Â Â Â Â Â Â Â Î±-glucosidase. However, Î±-glucosidase inhibitory activity in the extracts and fraction from leaves of the Garcinia kydia Roxb. has not been reported. In this study, seeks to evaluated of Î±-glucosidase inhibitory activity against extracts and fractions of potentially. Methods : The Î±-glucosidase inhibitory activity test, conducted by in-vitro using the enzymatic reaction is measured of quantity with a microplate reader and identify the compound from the active fraction with normal-phase thin layer chromatography. Results : The ethyl acetate and methanol extract have the potential to inhibit the Î±-glucosidase with the percent inhibition at a concentration of 500Î¼g/mL of 83 and 59%, respectively. The active fraction of the ethyl acetate extracts (FEA8) with percent inhibition at concentrations of 100 mg/mL and IC50 values of 80% and 2,79Î¼g/mL, respectively and active fraction of the methanol extracts (FMT3) with percent inhibition at concentrations of 100 mg/mL and IC50 values of 71% and 8,43 Î¼g/mL, respectively. Conclusion: Garcinia kydia Roxb. evident has the potential to inhibit the Î±-glucosidase. Flavonoid and phenolic compounds that suspected of acts as Î±-glucosidase inhibitory activity. Thus, the research will continue the process of isolating the active compound so that it can be developed as natural therapeutic agents in the control of glucose.